Yi-nao-jie-yu Prescription Exerts a Positive Effect on Neurogenesis by Regulating Notch Signals in the Hippocampus of Post-stroke Depression Rats - Tian, Huiling; Li, Xiaoli; Tang, Qisheng; Zhang, Wen; Li, Qingmeng; Sun, Xinyue; Zhao, Ruizhen; Ma, Chongyang; Liu, Haipeng; Gao, Yushan; Han, Fei (Frontiers in Psychiatry, 2018)
Post-stroke depression (PSD) is one of the most frequent complications of stroke. The Yi-nao-jie-yu prescription (YNJYP) is an herbal prescription widely used as a therapeutic agent against PSD in traditional Chinese medicine. Disruption of adult neurogenesis has attracted attention as a potential cause of cognitive pathophysiology in neurological and psychiatric disorders. The Notch signaling pathway plays an important role in neurogenesis. This study investigated the effects of YNJYP on adult neurogenesis and explored its underlying molecular mechanism in a rat model of PSD that is established by middle cerebral artery occlusion and accompanied by chronic immobilization stress for 1 week. At 2, 4, and 8 weeks, depression-like behavior was evaluated by a forced swim test (FST) and sucrose consumption test (SCT). Neurogenesis was observed by double immunofluorescence staining. Notch signals were detected by real-time polymerase chain reaction. The results show that, at 4 weeks, the immobility time in the FST for rats in the PSD group increased and the sucrose preference in the SCT decreased compared with that in the stroke group. Therefore, YNJYP decreased the immobility time and increased the sucrose preference of the PSD rats. Further, PSD interfered with neurogenesis and decreased the differentiation toward neurons of newly born cells in the hippocampal dentate gyrus, and increased the differentiation toward astrocytes, effects that were reversed by YNJYP, particularly at 4 weeks. At 2 weeks, compared with the stroke group, expression of target gene Hes5 mRNA transcripts in the PSD group decreased, but increased after treatment with YNJYP. At 4 weeks, compared with the stroke group, the expression of Notch receptor Notch1 mRNA transcripts in the PSD group decreased, but also increased after treatment with YNJYP. Overall, this study indicated that disturbed nerve regeneration, including the increased numbers of astrocytes and decrease numbers of neurons, is a mechanism of PSD, and Notch signaling genes dynamically regulate neurogenesis. Moreover, YNJYP can relieve depressive behavior in PSD rats, and exerts a positive effect on neurogenesis by dynamically regulating the expression of Notch signaling genes.